ANALISIS PERUBAHAN KURS RUPIAH TERHADAP DOLLAR AMERIKA - Triyono Triyono (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2008)
This research analyse influence of money supply, inflation, SBI rate of interest, and import to Indonesia Rupiah exchange rate to US Dollar. In analysis, used multiple regression analysis instrument with model Error Correction Model (ECM). With this method obtained equation of regression in long-run and short-run equilibrium. In the long run equilibrium model, covered series of adjustment process that bringing every shock to equilibrium. In other word, in the long run very possibly performed full adjustment to every changes in arising out. Estimation result from regression ECM and long-run analysis indicate that inflation variable, SBI rate of interest, and import have significant influence with positive direction to exchange rate. While variable JUB have influence with negative direction to exchange rate.